Impact of S-sulfocysteine on fragments and trisulfide bond linkages in monoclonal antibodies. Issue 6 (18th August 2017) - Seibel, Ronja; Maier, Sandra; Schnellbaecher, Alisa; Bohl, Susanne; Wehsling, Maria; Zeck, Anne; Zimmer, Aline
ABSTRACT: The quality of recombinant proteins such as monoclonal antibodies produced using Chinese hamster ovary cell-based mammalian systems is dependent on many factors, including cell line, process and cell culture media. Due to these factors, the generated product is heterogeneous and may have chemically-induced modifications or post-translational modifications that affect antibody stability, functionality and, in some cases, patient safety. This study demonstrates that S-sulfocysteine, a cysteine derivative, can increase the antibody specific productivity in different cell lines cultivated with different processes while minimizing trisulfide linkages in generated mAbs, mainly between heavy and light chain. The supplementation of a cell culture feed with S-sulfocysteine also proved to be useful to reduce the percentage of antibody fragments generated from the monoclonal antibody. Overall, this new component used in the upstream process allows a reduction of product heterogeneity.